Physicians' awareness of medication-related osteonecrosis of the jaw in patients with osteoporosis. - Nachapol Supanumpar; Pagaporn Pantuwadee Pisarnturakit; Natthinee Charatcharoenwitthaya; Keskanya Subbalekha (PLoS ONE)
A serious adverse effect of antiresorptive drugs, which are widely used to treat osteoporosis, is medication-related osteonecrosis of the jaw (MRONJ). Physicians can reduce the risk of MRONJ by educating patients and emphasizing the importance of good oral health. However, limited information is available regarding physicians' awareness and clinical practices associated with MRONJ. Hence, this study aimed to examine physicians' awareness related to MRONJ and associated clinical practices. This study was a cross-sectional study conducted from December 2022 to February 2023. An online self-administered questionnaire was sent to physicians in Thailand who prescribed antiresorptive drugs for osteoporosis. Most respondents agreed that antiresorptive drugs might cause MRONJ (92.3%), poor oral health increased the risk of MRONJ (84%), and MRONJ is an important consideration in patients with osteoporosis (85%). Of the respondents, 48.1% and 15.5% always referred patients to dentists before and during antiresorptive therapy, respectively. Approximately 60% of physicians informed patients of the MRONJ risk before prescribing antiresorptive drugs, and 30% inquired about patients' oral symptoms at the follow-up visit. Overall, 44% of physicians advised patients to receive oral health care; the most common reason for not advising this was that respondents did not consider themselves to be adequately knowledgeable to detect oral health problems. These findings indicate that while most physicians who prescribed antiresorptive drugs for osteoporosis were aware of and considered MRONJ in their practice, several took insufficient action to prevent it. This highlights the need to emphasize clinical practice guidelines and collaboration between physicians and dentists.